Marcia Davenport papers - Davenport, Marcia, 1903-1996.; Davenport, Marcia, 1903-1996.; Davenport, Marcia, 1903-1996.; Davenport, Marcia, 1903-1996.; Davenport, Marcia, 1903-1996.; Davenport, Marcia, 1903-1996.; Davenport, Marcia, 1903-1996.; Davenport, Marcia, 1903-1996.
Correspondence, literary manuscripts, galley proofs, working drafts, notes, and press clippings pertaining to Davenport's books and novels. Includes drafts of Mozart (1932); Of Lena Geyer (1936); The Valley of Decision (1942); East Side, West Side (1947); My Brother's Keeper (1954); Garibaldi; Father of Modern Italy (1957); and The Constant Image (1960). Correspondents include her agent, Carol Brandt, and Willa Cather, Irving Kolodin, Wallace Meyer, Montrose Jonas Moses, Maxwell Perkins, and Charles Scribner, Jr.
Author and music critic.
Collection material in English with Czech.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Brandt, Carol, -- 1904-1984 -- Correspondence; Cather, Willa, -- 1873-1947 -- Correspondence; Kolodin, Irving, -- 1908-1988 -- Correspondence; Meyer, Wallace -- Correspondence; Moses, Montrose Jonas, -- 1878-1934 -- Correspondence; Perkins, Maxwell E. -- 1884-1947 -- Correspondence; Scribner, Charles, -- 1890-1952 -- Correspondence; Authors and publishers; Authors; Music critics